Pengaruh Deep Back Massage Terhadap Penurunan Nyeri Persalinan Kala I Fase Aktive di BPM Pera Kota Medan Tahun 2024 - Basaria Manurung; Isyos Sari Sembiring; Emma Dosriamaya Noni Br Simanjuntak; Ninsah Mandala Putri Sembiring (PPNI UNIMMAN, 2024)
Childbirth is a process of expelling the results of conception (fetus and placenta), which can live to the outside world, from the uterus through the birth canal or by other means. During labor, the uterus contracts and pushes the baby down to the cervix. This study aims to determine the Effect of Deep Back Massage on Reducing Pain in the First Stage of Active Labor at BPM Pera, Medan City in 2024. This type of research is Experimental research. A research design used to find a causal relationship with the involvement of research in manipulating the independent variables. The population is 20 mothers giving birth at BPM Pera, Medan City in 2025, namely 10 people in the Treatment Group and 10 people in the Control Group. The data analysis technique uses t-test analysis. The results obtained in this study are the results of the t-test, namely the results of the paired test-test showed p = 0.011 (p <0.05) and t count = 11,768> from t table = 9,200 which proves that there is an effect of giving deep back massage on the level of labor pain in mothers who are giving birth to reduce labor pain.